Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Program Akuntansi Untuk Berkarir Sebagai Konsultan Pajak - Juliana; Viola Syukrina E Janrosl (Komunitas Dosen Indonesia, 2023)
Accounting is one of the majors that is in great demand by students in both public and private universities. Students enroll in accounting majors for a variety of reasons, including perceptions of a bright future for work, social prestige and economic progress. Professional accounting education will shape students to become experts in their field. The purpose of this study was to examine how perceptions, motivation, self-efficacy and labor market considerations can influence the career interests of accounting program students for careers as tax consultants. The research method used in this research is a quantitative research design, with primary and secondary data sources. The population in this study involved several students majoring in Accounting at tertiary institutions in Batam City in odd semesters totaling 612. In this study the technique of determining the sample size used the slovin formula with a total of 242 respondents. In this study, the sampling method used is a combination of non-probability sampling and purposive sampling approaches. Data analysis techniques used validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination analysis (R2), t test and f test. The results of the study state that perceptions, motivation, self-efficacy and labor market considerations can partially and simultaneously positively and significantly influence the career interest of accounting program students for a career as a tax consultant